Pengembangan Sistem Informasi Penerima Bantuan Sosial untuk Meningkatkan Transparansi dan Efisiensi Distribusi - Wahyuni, Asri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2022)
This study aims to develop and implement a Social Aid Recipient Information System to enhance transparency and efficiency in the distribution of social assistance. The system is designed to streamline the processes involved in identifying, registering, and managing recipients of social aid. Key features include a comprehensive recipient database, automated eligibility verification, real-time tracking of aid distribution, and detailed reporting capabilities. By integrating advanced data management and biometric authentication technologies, the system ensures accurate identification and prevents fraud. The research discusses the design, development, and deployment phases of the system, including the selection of appropriate technologies, system architecture, and user interface design. The system is evaluated based on its impact on operational efficiency, transparency, and user satisfaction. The results indicate that the implementation of the Social Aid Recipient Information System leads to significant improvements in the distribution process, ensuring that aid reaches the intended beneficiaries in a timely and efficient manner. The paper also addresses the challenges encountered during the development and deployment phases, as well as the solutions implemented to ensure successful integration and user adoption.